Textualism, extratextualism, and the fiction/nonfiction distinction in documentary studies. Issue 2 (4th May 2021) - Slugan, Mario
ABSTRACT: This article critiques existing textualist and extratextualist (intentionalist and reception-driven) approaches to capturing the ordinary understanding of the fiction/nonfiction distinction in philosophical and film scholarship on documentary and offers an alternative extratextualist approach dubbed institutionalism. I argue that textualist attempts fail because no textual element (presentational strategy, misrepresentation, staging, or indexicality) is necessarily either fictive or nonfictive. Intentionalism falls short because films can change their non/fictional status over time (e.g. phantom rides). Finally, reception-driven approaches confuse personal categorizations for public ones. The proposed institutionalism, by contrast, combines the strengths of moderate textualism and reception-driven theories (allowing for the changing status of documentary and nonfiction) with those of intentionalism (denying that some textual elements are necessarily fictive and others nonfictive) to capture the ordinary understanding of the fiction/nonfiction distinction.